Chronic fistula of the right iliac fossa: Ceco-appendicular cancer - Croci, Fabio; Pressa, Carlos; González, Luis; Bermúdez, Jorge (Cirugía del Uruguay, 1986)
Authors present an spontaneous colo-cutaneous flslula of right lllac fossa preceded by an abscedatlon of internal lliac fossa in a man aged 48 and taken for an abscess of appendicular origin, the barium enema of the coion and flbrocolonoscopy not evidencing any cecal lesion. 11 was diagnosed by the histological examinatlon of the flstulous trajectory. A cllnlcal, pathologlcal and prevlslon report is made In respect of this rare occurrence.